Приватизация как источник финансирования дефицита государственного бюджета Украины - Корчинский, В.Е.; Попов, А.В. (Культура народов Причерноморья, 2013)
В представленной работе рассматривается дефицит бюджета как экономическое
явление. Исследуется приватизация как один из источников финансирования дефицита
Государственного бюджета Украины. Делаются выводы по направлению уменьшения дефицита
государственного бюджета. Основными факторами, негативно влияющими на рост дефицита
государственного бюджета, является экономическая и политическая нестабильность, несовершенство
законодательной базы, невзвешенная бюджетная политика.
Ключевые слова: государственный бюджет Украины, приватизация, бюджетный дефицит,
государственный долг. У представленій роботі розглядається дефіцит бюджету як економічне явище.
Досліджується приватизація як одна з джерел фінансування дефіциту Державного бюджету України.
Робляться висновки по напрямку зменшення дефіциту державного бюджету. Основними факторами,
що негативно впливають на зростання дефіциту державного бюджету, є економічна і політична
нестабільність, недосконалість законодавчої бази, невиважена бюджетна політика.
Ключові слова: державний бюджет України, приватизація, бюджетний дефіцит, державний борг. In the present paper we consider the budget deficit as an economic phenomenon. Examines
privatization as one of the sources of financing the deficit of the State Budget of Ukraine. Conclusions are drawn
in the direction of reducing the budget deficit. One of the most important instruments of state financial policies
affecting the economic and social situation of the country is the state budget deficit. The financial crisis,
unbalanced economic and social policies, the decline of manufacturing and industry are the reasons of
exceeding the state budget deficit, and as a consequence, the existence of the state budget deficit. Therefore,
issues analysis deficit state budget today is quite relevant. Purpose of the article is to study the following issues:
the current level of government deficits; analysis of the sources of financing of the budget deficit; development of
proposals about the overcome the deficit; assessment of privatization as one of the sources of financing the
deficit of the State Budget of Ukraine. Budget deficit – the almost constant phenomenon in the economy of each
state. For the population deficit is mediated by the value. Nevertheless, the population is involved in the return of
borrowed funds to cover the shortfall by paying taxes. Budget in Ukraine can be approved with a deficit only if
there are reasonable sources of financing. The causes of the deficit may be the following: delay in the
implementation of structural changes in the economy or technology enhancement; a decline in production,
decrease the efficiency of individual sectors; the high military spending, the financial and economic instability in
the world. Financing of the budget deficit is possible with various methods, including through privatization. The
most important ways of financing the deficit are: attraction of loans; the State's active operations (refunds from
deposits with domestic and foreign banks, issue securities in order to generate revenue); use of the funds
accumulated in the treasury account of the government. Despite the fact that it is still in the Ukraine the main
sources of financing the budget deficit is the internal and external borrowing, recently the privatization of state
property has taken its place in the sources of replenishment of the budget deficit.
Keywords: state Budget of Ukraine, privatization, budget deficit.